An Integrated Environment for Learning Design - Hernández-Leo, Davinia; Asensio-Pérez, Juan I.; Derntl, Michael; Pozzi, Francesca; Chacón, Jonathan; Prieto, Luis P.; Persico, Donatella (Frontiers in ICT, 2018)
Learning design tools aim at supporting practitioners in their task of creating more innovative and effective computer-supported learning situations. Despite there is a myriad of proposed tools, their use presents challenges that recent studies link with practitioners' varied pedagogical approaches and context restrictions, as well as with barriers to practical application derived from the fact that most tools only cover limited functionality and do not support cooperation between practitioners. In this paper we investigate whether it is possible to provide a flexible community system that supports multiple learning design tasks. We propose an Integrated Learning Design Environment (ILDE), which is a networked system integrating collaboration functions, design editors and middleware that enables deployment of the designed learning situations into Virtual Learning Environments. We describe the iterative user-centered process adopted in the design of ILDE as well as its architecture. The architecture is implemented to show its feasibility and that it is capable of providing the targeted functionality. We also present the results of its use in training workshops with 148 practitioners from five different institutions in vocational training, higher and adult education. Some of the designs were deployed in VLEs and enacted with students in real learning situations.